Artistic Function of Implicit Reference in Orhan Pamuk's Novel “My Name is Red” - Susareishvili, Maka (Bulletin of Akaki Tsereteli State University, 2025)
The novel "My Name is Red" is of postmodernist nature. Intertextual discourse methods are found in the work: explicit and implicit references. The artistic function of implicit reference serves to enrich the narrative, to contextualize the plot in a specific cultural and historical environment. Through references, the ideological connections between the donor and referent texts are brought to life. Reference is the best way to verbalize an artistic idea.